Data-Based Modelling of Ship Propulsion for A 2500 TEU Feeder Container Ship - Jefferson Marcel Soadamara; Wolfgang Busse; Karsten Wehner (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2020)
A sea-going vessel will always face the risk of rough weather along with its voyages. The focus of this paper is on the creation of a data-based model to estimate the power increase or speed loss due to the influence of weather, by using resistance estimation theories and added resistance approximation methods along with additional assisting tools. Furthermore, a theoretical simulation is done in order to benchmark and correct the model setup. The analysis of simulation results shows that at the available data range, the model proves reasonably precise within its capabilities, for academic applications. The general behavior of the model complies with common ship theory, however, does not perfectly resemble the speed-power relation of the ship’s recorded data averages. The analysis suggests that the model is most compatible with the shipload draft of 9,0 to 9,5 meters and within the speed of 19 to 22 knots. The lack of data outside the typical operating range disables the ability to verify the model correspondingly. The theoretical simulation proves valuable in assessing ship data-based models.